The Federal Trade Commission a Critical Survey - Watkins, Myron W. (Quarterly Journal of Economics, 1926)
I. Genesis of Federal Trade Commission law, 562. — II. Value of investigations made by Economic Division, 566. — Proceedings instituted by Legal Division mainly for protection of customers, rather than competitors, 568. — Regulative policies unsoundly drawn in three directions, 571. — Principal criticism is of failure of Commission to define limits of its corrective responsibility, 574. — Accomplishments of Commission as an advisory and consultative body, 578. — Significance of recent changes in rules of procedure, 579. — III. How inflexibility and lack of dispatch in administrative procedure may be overcome, 580. — Some suggestions toward substantive amendment of Clayton and Federal Trade Commission Acts, 584.